Advances in extraction, utilization, and development of chitin/chitosan and its derivatives from shrimp shell waste - Gao, Mingyue; Tang, Hanqi; Zhu, Hongguang (Comprehensive reviews in food science and food safety, 2024)
Shrimp consumption is in great demand among the seafood used globally. However, this expansion has resulted in the substantial generation and disposal of shrimp shell waste. Through literature search, it has been observed that since 2020, global scholars have shown unprecedented interest in shrimp shell waste and its chitin/chitosan. However, these new insights lack corresponding and comprehensive summarization and analysis. Therefore, this article provides a detailed review of the extraction methods, applications, and the latest research developments on chitin/chitosan from shrimp shells, including micro‐nano derivatives, from 2020 to the present. The results indicate that chemical extraction remains the primary technique for the extraction and preparation of chitin/chitosan from shrimp shells. With further refinement and development, adjusting parameters in the chemical extraction process or employing auxiliary techniques such as microwave and radiation enable the customization of target products with different characteristics (e.g., deacetylation degree, molecular weight, and degree of acetylation) according to specific needs. Additionally, in pursuit of environmentally friendly, efficient, and gentle extraction processes, recent research has shifted toward microbial fermentation and green solvent methods for chitin/chitosan extraction. Beyond the traditional antibacterial, film‐forming, and encapsulation functionalities, research into the applications of chitosan in biomedical, food processing, new materials, water treatment, and adsorption fields is gradually deepening. Chitin/chitosan derivatives and their modified products have also been a focal point of research in recent years. However, with the rapid expansion, the future development of chitin/chitosan and its derivatives still faces challenges related to the unclear mechanism of action and the complexities associated with industrial scale‐up.